Internal and external loads in professional women's Rugby Sevens: analysis of a block-based training session with small games - Filipe Oliveira Bicudo; Lucas Savassi Figueiredo; Lucieli Teresa Cambri; Jacielle Carolina Ferreira; Ana Paula da Silva Azevedo; Gustavo Ferreira Pedrosa; Samuel da Silva Aguiar; Henrique de Oliveira Castro (Termedia Publishing House, 2024)
Purpose This study aimed to compare internal load (IL) and external load (EL) variables between blocks of a game-based Rugby Sevens training session. Methods A descriptive cross-sectional study design was employed. Twenty-eight professional athletes from the first division of the Brazilian national championship were monitored during a game-based training session, which consisted of varying durations of ball-in-play blocks. The training session comprised 4 blocks of 1 min, 2 blocks of 2 min, and 1 block of 3 min of ball-in-play, with 1-min intervals between blocks of the same duration and 2-min intervals between blocks of different durations. Results A reduction in EL was reported during longer bouts of ball-in-play. Specifically, a reduction was observed when comparing block 5 to block 1 ( p = 0.021) and when comparing block 7 with blocks 1, 2, 3, 4, and 6 for distance per min. For accelerations and decelerations, blocks 5, 6, and 7 showed lower values than block 1 ( p = 0.001 and p = 0.005, respectively). Block 4 showed an increase in rate of perceived exertion (RPE) values compared to blocks 1 ( p = 0.010) and 2 ( p = 0.004). Increased RPE values were also found in block 5 compared to block 1 ( p = 0.001), as well as compared to blocks 2 ( p = 0.001) and 3 ( p = 0.002). RPE in block 7 was higher than in blocks 1, 2, 3, and 4 ( p = 0.001). Conclusions In summary, higher RPE values were reported across blocks, and IL appeared to be more volume-dependent.